Role of Tissue Specific Plantar Fascia Stretching Exercises Versus Myofascial Released Technique in Chronic Plantar Fasciitis - Muhammad Khan; Syed Shahzad Ali; Rabail Rani Soomro (Journal of Basic & Applied Sciences, 2021)
Objective: The effectiveness of tissue specific stretching exercises and myofascial released technique on intensity of pain and Foot function was compared in chronic plantar fasciitis patients. Study Design: Randomized controlled trial study Place and Duration of Study: This study was conducted at Al-Ain Poly clinic Karachi between 2012-13. Materials and Methods: Fifty patients with chronic plantar fasciitis were enrolled through convenience sampling and were randomly assigned into Stretching Exercise and Myofascial Release Technique groups. Intensity of pain and foot function were evaluated by Visual Analouge Scale and foot function index, respectively. Ten sessions were done for both groups. T-tests and ANCOVA test were used for statistical analysis (p<0.05). Results: The score of visual analogue scale (VAS) and foot functioning index (FFI) improved in both groups, though the decrease of intensity of pain was more in stretching exercises Group (p<0.01). Additionally, improvement in foot functioning index did not significantly differ between two groups. Conclusion: The stretching exercises can reduce pain and improve foot functioning in chronic plantar fasciitis.